Behavior of adult and young grassland songbirds at fledging. Issue 2 (13th March 2019) - Ribic, Christine A.; Rugg, David J.; Koper, Nicola; Ellison, Kevin; Ng, Christoph S.
Abstract: The behavior of adults and young at the time of fledging is one of the least understood aspects of the breeding ecology of birds. Current hypotheses propose that fledging occurs either as a result of parent‐offspring conflict or nestling choice. We used video recordings to monitor the behavior of nestling and adult grassland songbirds at the time of fledging. We observed 525 nestlings from 166 nests of 15 bird species nesting in grasslands of Alberta, Canada, and Wisconsin, USA. Overall, 78% of nestlings used terrestrial locomotion for fledging and 22% used wing‐assisted locomotion. Species varied in propensity for using wing‐assisted locomotion when fledging, with nestling Grasshopper Sparrows ( Ammodramus savannarum ) and Henslow's Sparrows ( Centronyx henslowii ) often doing so (47% of fledgings) and nestling Song Sparrows ( Melospiza melodia ), Common Yellowthroats ( Geothlypis trichas ), and Chestnut‐collared Longspurs ( Calcarius ornatus ) rarely doing so (3.5% of fledgings). For 390 fledging events at 127 nests, camera placement allowed adults near nests to be observed. Of these, most young fledged (81.5%) when no adult was present at nests. Of 72 fledging events that occurred when an adult was either at or approaching a nest, 49 (68.1%) involved feeding. Of those 49 fledgings, 30 (62.1%) occurred when one or more nestlings jumped or ran from nests to be fed as an adult approached nests. The low probability of nestlings fledging while an adult was at nests, and the tendency of young to jump or run from nests when adults did approach nests with food minimize opportunities for parents to withhold food to motivate nestlings to fledge. These results suggest that the nestling choice hypothesis best explains fledging by nestlings of ground‐nesting grassland songbirds, and fledging results in families shifting from being place‐based to being mobile and spatially dispersed. RESUMEN: Comportamiento de pájaros de pastizal adultos y juveniles al emanciparse El comportamiento de adultos y jóvenes al momento de la emancipación es uno de los aspectos menos comprendidos de la ecología reproductiva de las aves. Las hipótesis vigentes proponen que la emancipación ocurre por conflicto padres‐progenie o por la propia elección del polluelo. Usamos videograbaciones para monitorear el comportamiento de polluelos y adultos de aves de pradera al momento de abandonar el nido. Observamos 525 polluelos de 166 nidos de 15 especies de aves anidando en las praderas de Alberta, Canadá y Wisconsin, Estados Unidos. En total, 78% de los polluelos usaron la locomoción terrestre para dejar el nido y el 22% usaron locomoción asistida por sus propias alas. Las especies variaron en cuán propensas eran a usar la locomoción asistida por sus alas al emanciparse, con dos especies de gorriones Ammodramus savannarum y Centronyx henslowii haciéndolo frecuentemente (47% de los polluelos) y los polluelos del gorrión Melospiza melodia, la mascarita Geothlypis trichas y el escribano Calcarius ornatus haciéndolo raramente (3.5% de los polluelos). De 390 eventos de emancipación en 127 nidos, la localización de las cámaras permitió la observación de adultos cerca del nido. De éstos, la mayoría de los polluelos (81.5%) se emanciparon cuando no había adultos presentes en el nido. De 72 eventos de emancipación que ocurrieron cuando un adulto se encontraba en el nido o acerándose a éste, en 49 (68.1%) mediaba la alimentación. De esos 49 polluelos, 30 (62.1%) ocurrieron cuando uno o más polluelos saltaron o corrieron de sus nidos para ser alimentados cuando algún adulto se acercaba al nido. La baja probabilidad de abandonar el nido cuando un adulto estaba en el nido, y la tendencia de los juveniles por saltar o correr de los nidos cuando los adultos se aproximaban con comida para reducir las oportunidades de los adultos de retener la comida y motivar a los polluelos a emanciparse, sugieren que los patrones de emancipación de pájaros de pradera que anidan en el suelo apoyan la hipótesis de la elección del polluelo en la que la emancipación resulta en familias dejando de estar basadas en un sitio a ser más móviles y espacialmente dispersas.